Posterior Reversible Encephalopathy Syndrome Complicating Ruptured Appendicitis and Abscess Drainage in a Previously Healthy Pediatric Patient - Saley, Taylor; Barton, Alexander; Sood, Shawn Berry; Thukaram, Roopa (Journal of Pediatric Intensive Care, 2019)
In this study, we present the youngest reported case of posterior reversible encephalopathy syndrome (PRES) in the United States, which developed following perforated appendicitis with subsequent peritonitis and intra-abdominal abscess formation. Additionally, we discuss potential physiological factors contributing to her acute neurological deterioration and resultant cerebral vasogenic edema.
Keywords: autoregulation; endothelium; seizures; sepsis; PRES